Pemberdayaan Masyarakat dalam Pencegahan Kekerasan Seksual Melalui Program Edukasi dan Konseling Berbasis Gender di Pondok Pesantren Assanahdiyah Sebrang ULU II Palembang - Rotua Lenawati Tindaon; Dina Supriyati; Eva Elfrida Pardede; Adelina Irmayani Lubis; Umi Solekah (Lembaga Pengembangan Kinerja Dosen, 2025)
The World Health Organization (WHO) states that approximately 1 in 3 women worldwide have experienced physical or sexual violence during their lifetime. One preventative measure considered effective is gender-based education. This education emphasizes understanding equality between men and women, respect for individual rights, and awareness of the risks and prevention of sexual violence.The socialization approach, training, technology implementation, mentoring, and program sustainability methods ensure that community empowerment in preventing sexual violence can run effectively.The results of the analysis show that most respondents are in the category Tall , which indicates that gender-based education and counseling programs have had a positive influence on the knowledge, attitudes, and awareness of young people in preventing sexual violence. In addition to statistical data, pretest and posttest data were used to conduct the test analysis based on the results. Paired t-test, obtained valuep = 0.000 (< 0.05), indicating a significant difference between scores before and after the education and counseling program. Respondents demonstrated a good understanding of the forms of sexual violence, the right to refuse unwanted touching, and the importance of seeking help when an incident of sexual violence occurs. It is recommended that this program be continued and expanded to other faculties or institutions.